Bibliographie der Arbeiten von Professor Stefan Kowal [Bibliography of the works of Professor Stefan Kowal] - Powaga, Alina (Studia Historiae Oeconomicae, 2009)
Bibliography of the works of Professor Stefan Kowal 1967-2008